Transportation Issues: Perspectives of Orientation and Mobility Providers. (November 2015) - Crudden, Adele
Introduction: This is an exploratory study of orientation and mobility (O&M) providers' perceptions of transportation issues for persons who are blind or have low vision. Transportation challenges, particularly regarding employment, are examined, the role of O&M providers are explored, and strategies to address these barriers are suggested. Methods: Six O&M providers volunteered to participate in a focus group conducted at a national conference. Transcripts of their remarks were coded and themes associated with the research questions were identified and reported. Results: Limitations of public transportation and the cost of transportation were viewed as major barriers to accessing transportation, particularly regarding employment, but safety issues and stress associated with transportation were also concerns. Involvement of O&M providers in securing transportation varied; most were not directly involved in the process. Most visually impaired persons received instruction in the use of fixed-route transportation systems during O&M instruction regardless of availability. Discussion: Living in areas with accessible public transportation, self-advocacy, and using bioptics to drive should be explored as they may be helpful in overcoming transportation barriers. People who are visually impaired are not routinely engaged in dialogue with O&M providers about the strategies needed to identify and negotiate the transportation options available to them. Implications for practitioners: Engaging visually impaired people in discussions that focus on problem-solving skills, such as how to negotiate rides or find a driver, may be helpful to them in overcoming transportation barriers. Further research to determine who should be responsible for facilitating these conversations is warranted, as well as research regarding drivers' attitudes about liability and the impact of bioptics on rehabilitation outcomes. Vision rehabilitation counselors may need training about how to screen consumers for referral for potential use of bioptics to enable driving.